THE LIMITS OF THE FORMAL TREATMENT OF LANGUAGE - P. Alpár GERGELY (Studia Universitatis Babeș-Bolyai. Philosophia, 2019)
The Limits of the Formal Treatment of Language. Within the philosophy of language, there is a distinction between the natural language philosophers and the ideal language philosophers. The distinction is drawn based on the way these philosophers reflect on language and the world. Natural language philosophers stress the context-based feature of meaning, while the ideal language philosophers emphasize the context-free feature of meaning. In my study I want to show that that even within the formal study of language, in the apparent absence of any context, the notions of valuation and interpretation help us to understand the meaning of sentences.